Risk factors for mortality in patients with pulmonary infections with non-tuberculous mycobacteria: A retrospective cohort study. Issue 1 (January 2015) - Gommans, E.P.A.T.; Even, P.; Linssen, C.F.M.; van Dessel, H.; van Haren, E.; de Vries, G.J.; Dingemans, A.M.C.; Kotz, D.; Rohde, G.G.U.
Summary Background Infections with non-tuberculous mycobacteria (NTM) represent an increasing problem. Their clinical relevance is still largely unknown as well as predictors for mortality in affected patients. The objective was to describe prevalence and clinical relevance of different NTM and to identify risk factors for mortality. Methods Retrospective cohort study of 124 patients with NTM detection between January 2001 and December 2011. Clinical characteristics like symptoms and radiological appearance were assessed at presentation. The primary outcome was all cause mortality during the follow-up period. Univariate and multivariate survival analyses using Cox proportional hazard models were employed for statistical analysis. Results Over the study period, the frequency of NTM isolation varied from 4 to 12 patients per year. Twenty-nine out of 124 patients (23%) had a clinically relevant infection, according to the criteria of the American Thoracic Society (ATS). Mycobacterium avium was isolated most frequently, but Mycobacterium kansasii, Mycobacterium malmoense and Mycobacterium xenopi had the highest clinical relevance. Symptoms were mostly diverse and non-specific. On radiology, cavities were observed more frequently than a nodular-bronchiectatic variant or consolidation. In 75% of all patients, follow up time was more than two years. Median survival was 6.5 years (95%CI = 2.7–10.3). Factors significantly influencing survival time were haemoptysis (HR = 0.2, 95%CI = 0.1–0.6) and a consolidation on imaging (HR = 5.1, 95%CI 1.4–18.2). Conclusions The presentation of an infection with NTM can be diverse and depends mainly on the causative NTM pathogen. The most important predictor for increased mortality is the radiological appearance of a consolidation.